KEGIATAN BERMAIN MATEMATIKA - SARI, RATIH PERMATA (JPUD - Jurnal Pendidikan Usia Dini, 2013)
This study aims to describe the implementation of practices in terms of mathematicrelated playing activities, in terms of the locations, the participation of children, games being used, and the principles of early childhood mathematics instruction based on the level of development of children, as practiced in R.A. Kartini Aisyiyah Kindergarten 21, Malang. This type of research is a form of qualitative research case study. The results include: learning activities applied by teachers using the concept of learning by playing, both indoor and outdoor, and either individually or collectively. The games-augmented playing activities are designed along the concept of jovial playful ambiance, corresponds to the developmental characteristics of children aged 4 -5 years. Key words: playing math, case study. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan kegiatan bermain matematika yang meliputi lokasi, partisipasi anak, permainan yang digunakan, dan prinsip-prinsip pembelajaran matematika anak usia dini berdasarkan tingkat perkembangan anak, seperti yang dilakukan di RA Kartini Aisyiyah TK 21, Malang. Jenis penelitian ini adalah penelitian kualitatif studi kasus. Hasil penelitian meliputi: kegiatan belajar yang diterapkan oleh guru menggunakan konsep belajar dengan bermain, baik indoor maupun outdoor dan baik secara individual maupun kolektif. Kegiatan bermain game dirancang sepanjang konsep riang suasana menyenangkan, sesuai dengan karakteristik perkembangan anak usia 4 -5 tahun. Kata kunci: bermain matematika, studi kasus